Pleiotropic Modulation of Carbon and Nitrogen Metabolism in Arabidopsis Plants Overexpressing the NAD kinase2 Gene - Takahashi, Hideyuki (American Society of Plant Biologists, 2009)
Nicotinamide nucleotides (NAD and NADP) are important cofactors in many metabolic processes in living organisms. In this study, we analyzed transgenic Arabidopsis (Arabidopsis thaliana) plants that overexpress NAD kinase2 (NADK2), an enzyme that catalyzes the synthesis of NADP from NAD in chloroplasts, to investigate the impacts of altering NADP level on plant metabolism. Metabolite profiling revealed that NADP(H) concentrations were proportional to NADK activity in NADK2 overexpressors and in the nadk2 mutant. Several metabolites associated with the Calvin cycle were also higher in the overexpressors, accompanied by an increase in overall Rubisco activity. Furthermore, enhanced NADP(H) production due to NADK2 overexpression increased nitrogen assimilation. Glutamine and glutamate concentrations, as well as some other amino acids, were higher in the overexpressors. These results indicate that overexpression of NADK2 either directly or indirectly stimulates carbon and nitrogen assimilation in Arabidopsis under restricted conditions. Importantly, since neither up-regulation nor down-regulation of NADK2 activity affected the sum amount of NAD and NADP or the redox state, the absolute level of NADP and/or the NADP/NAD ratio likely plays a key role in regulating plant metabolism.